1967
DOI: 10.1029/jz072i010p02547
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the western Somali Basin

Abstract: The western Somali Basin in the northwestern Indian Ocean is covered by thick deposits of terrigenous sediments. Seismic reflection profiles show, however, the northern and southern parts to be very different. The northern sections is a deep basin filled with thick uniformly stratified sediments. It is enclosed by the continental margin to the west and north, Chain ridge to the east, and shallow basement structure to the south. A change in depth of basement occurs along an approximately east‐west line at latit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…The break-up of the African plate to form the Red Sea and Gulf of Aden must have occurred during the recent spreading period. The sediment distribution in the Western Somalia basin discussed by Bunce et al (1967) agrees with the history derived from the magnetic lineations. They found that the thick sediments in the Somali Abyssal Plain thinned eastwards where large magnetic anomalies were observed (Bunce et al 1967 , Fig.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…The break-up of the African plate to form the Red Sea and Gulf of Aden must have occurred during the recent spreading period. The sediment distribution in the Western Somalia basin discussed by Bunce et al (1967) agrees with the history derived from the magnetic lineations. They found that the thick sediments in the Somali Abyssal Plain thinned eastwards where large magnetic anomalies were observed (Bunce et al 1967 , Fig.…”
supporting
confidence: 78%
“…The other major feature of the Arabian Sea-floor is the Owen fracture zone (Matthews 1966), which separates Arabia from the greater part of the Arabian Sea, and is also weakly seismic. Matthews suggested the Chain ridge, which lies to the south of the Carlsberg ridge and is not seismically active, forms the southern extension of Owen fracture zone, though others (Bunce et al 1967) do not agree. The northern boundary of the Arabian Sea is the eastward continuation of the Zagros fold belt, and is the only boundary of the sea which is at present a plate boundary.…”
Section: The Arabian Seamentioning
confidence: 99%
See 1 more Smart Citation
“…Very little can be said about the westernmost Indian Ocean. It is, however, probable that Madagascar and the Seychelles were detached from the African continent in the earliest phase of drift, as suggested by the large sediment accumula,tions [Bunce et al, 1967] and the recovery of various samples of Mesozoic sediments (Figure la).…”
Section: ) the Change Of The Pole Of Rotation To 26øn 21øementioning
confidence: 99%
“…The Northern Somali Basin has been described by Bunce et al [1966Bunce et al [ , 1967. They found that it is characterized by a flat abyssal plain morphology underlain by about 2 s of flat layered sediments.…”
Section: Introductionmentioning
confidence: 99%